Breath Smoke Detection: Non-Invasive Assessment of Substances Found in Cigarettes - Rizka Nurul Hidayah (Journal of Medicine and Health Technology, 2026)
Breath analysis not only holds great potential for the development of new non-invasive diagnostic methods, but also for the identification and follow up of drug levels in breath. This is of interest for both, forensic and medical science. On the one hand, the detection of drugs of abuse in exhaled breath-similar to the well-known breath alcohol tests-would be highly desirable as an alternative to blood or urine analysis in situations such as police controls for drugged driving. Despite the many benefits and conveniences offered, the use of this useful tool is currently still very rare and requires shipping from abroad. Development is needed to realize it in a more affordable version, so researchers discuss further in this paper